Preliminary experience on laparoscopic pancreaticoduodenal combined with major venous resection and reconstruction anastomosis - Peng, Xuehui; He, Yonggang; Tang, Yichen; Yang, Xiaomin; Huang, Wen; Li, Jing; Zheng, Lu; Huang, Xiaobing (Frontiers in Surgery, 2022)
Objective This study aims to summarize our experience in laparoscopic pancreatoduodenectomy (LPD) combined with major venous resection and reconstruction, as well as to evaluate its safety and discuss the surgical approach. Methods We retrospectively analyzed 14 cases of patients diagnosed with pancreatic tumors invaded the superior mesenteric vein or portal vein who had undergone LPD combined with major venous resection and reconstruction in our center from May 2016 to May 2020. Clinical data of these 14 patients were collected and analyzed, including general information (age, gender, pathological diagnosis, body mass index, etc.), intraoperative data (operation time, intraoperative blood loss, transit rate, blood transfusion, tumor diameter, R0 resection rate, cleaning lymph node number, removal vessel length, venous reconstruction time), and postoperative results (gastrointestinal function recovery, postoperative hospital time, complications, and fatality rate). Patients were followed up after surgery, and data were collected for statistical analysis. Results A total of 14 patients (9 males and 5 females) received LPD combined with major venous resection and reconstruction by arterial approach. The mean age was 52.5 (43–74) years old. Three of these 14 patients had routine wedge resection, 9 had opposite-to-end anastomosis after venous resection, 2 had artificial venous replacement, and the average length of removal vessel was 3.1 (2–4.5) cm. The operation time was 395 (310–570) min; the venous blocking time was 29.7 (26–50) min; the hospitalization stay was 13.6 (9–39) days. There was no grade B or C postoperative pancreatic fistula (POPF) that occurred, only one patient had biochemical fistula. One patient had upper gastrointestinal bleeding after subcutaneous injection of low molecular weight (LMW) heparin, and the condition was alleviated after conservative treatment, and one had pulmonary infection. The 12-month disease-free survival rate was 85.7%, and the 12-month overall survival rate was 92.8%. No patients had 30-day re-admission or death. Conclusion On the basis of the surgeon’s proficiency in open pancreatoduodenectomy combined with venous resection and reconstruction and standard LPD, the arterial approach for LPD combined with major venous resection and reconstruction is safe and feasible.